Historiografia crítica : breve estudo do pensamento marxista sobre o Brasil de 1500 a 1822 - Pansera, Tiago (2011)
Marxists´ historygraphics production elaborated during 20 century about Brazil‟s history became sources of historical resources, characterized by analysis, interpretation, and singular methods. Investigating their mean knowing and recognize the existence, effectively and the wide of this thought current knowing, that produced an economically history and class´ fight in Brazil, but, it is related to a past without wide with the present because of the historygraphics models currently. In critical historygraphic: a brief study of Marxist thought about Brazil (1500-1964) it discussed about a large chronologic space, from 1500 to 1964, because to know the economic, political and social history is a primary condition to understand the social formation and the singularities in a manner to produce hegemonic in contemporary Brazil. In a same way, the comprehension of Marxism historygraphic thought and their nuances allowed to analyze classic works without became them right, advance into the theoretical discuss and epistemological. It was identified similarities among writes produced before and during the military dictatorship of 1964. In many cases they were militaries of left politic organization, with emphasis to Comunista do Brasil Party (PCB). These intellectual did not produce only the history to fill out the books pages, or receive academic titles. They wrote with the purpose to contribute in solving historygraphics contradictions in theories and national development socioeconomic. Into these works some authors, such as Alberto Passos Guimarães and Nelson Werneck Sodré, it was possible to comprehend the next link with the Party line‟s thought and the almost became Marxist thought right. Beyond, in relation to plan to historic development of societies, and their respective manners of production, identified by Karl Marx in a specific case of Europe. In others places, with emphasis to Jacob Gorender´s writes, many epistemological of Marxist contradictions were overcame by large and systematic studies about Brazil history